Smart mixes in international supply chains: A definition and analytical tool, illustrated with the example of organic imports into Switzerland - Robert Home; Mareike Weiner; Christian Schader (Administrative Sciences, 2021)
Combinations of national and international, hard and soft powers, known as Smart Mixes, have been proposed as a way for governments in consumer countries to influence the behaviour of supply chain actors who operate outside their jurisdiction. However, the Smart Mix concept has not yet been precisely defined, which has hindered its operationalization as a means of analyzing the governance of long and complex international supply chains. The aim of this contribution is to derive a working definition of Smart Mixes and use it to create and demonstrate a generalizable analytical tool that facilitates identification of whether a Smart Mix exists in an international supply chain. To address this aim, we reviewed existing literature on Smart Mixes to define the concept, which led to a three-step process for analyzing a supply chain. In a second stage, we demonstrate the process by applying it to the example of organic imports into Switzerland, using data from expert interviews and existing public documentation. The application showed that the governance of the organic sector in Switzerland related to imported products fulfils the criteria for it to be considered a Smart Mix that enables the Swiss Government to influence the behaviour of supply chain actors outside its jurisdiction. This example shows that the proposed Smart Mix concept is sound under particular circumstances: in this case, when the interests of the public and private sectors are aligned so that binding public measures provide protection to the private sector. These circumstances are not unique to organic imports into Switzerland, which allows the conclusion that Smart Mixes may provide sustainability solutions in other international supply chains.
Keywords: 350; international supply chain; organic; smart mix; sustainability; Switzerland; voluntary measures